Decade floatings and its comparison with the minimum temperature average in amparo de São Francisco, Sergipe – Brazil (Research, Society and Development, 2021)
In the last few decades, climate change and its consequences for humanity, has been one of the major concerns of scientists worldwide. The objective is to analyze the decadal variability using the time series of the minimum temperature 1963-1972; 1973-1982; 1983-1992; 1993-2002; 2003-2012 and 2013-2020 and compared with the historical average of 1960-2018. The thermal data estimated by the Estima_T software for 1963-2020 were used, followed by their decaying calculations for the decades already described, followed by the annual distribution, anomaly and their annual percentage. The minimum temperature of the study area shows changes in its oscillations in the early morning period, leaving the weather more unstable and warmed by the dawn in the last decade. The fluctuations in the minimum air temperature result from the synoptic systems operating at the time of the rainy and dry periods, as well as from the impacts on the environment, and these fluctuations may be related to the factors causing and / or inhibiting the interregional pliviometric indices. The thermal anomalies recorded in the first decades were due to natural factors, over the decades the effect of urbanization and interiorization was notorious, intensifying the effect of anomalies due to anthropic effects.